The immunomodulatory p43 secreted protein of Trichuris whipworm parasites is a lipid carrier that binds signalling lipids and precursors - Malcolm W. Kennedy; Allison J. Bancroft; Richard K. Grencis (Scientific Reports)
Abstract Trichuris whipworms cause disease and morbidity in humans and other animals. Their prolonged intestinal infections persist despite intact immune systems of their hosts and are attributed to immunomodulatory activities of their secretions. The p43 (Tm-DLP-1) protein of Trichuris muris of mice comprises 95% of the protein secreted by adult parasites, binds matrix proteoglycans, and has immune cytokine (IL-13)-neutralising activity. Using fluorescence-based methods we show that p43 binds fatty acids and retinol, including signalling lipids or precursors thereof. The orthologue of p43 from the human whipworm, Trichuris trichiura, exhibits similar lipid-binding activity. From the known molecular structure of p43, we explore the existence of extensive surface-accessible cavities with diverse surface charge characteristics which may indicate binding of diverse small molecule types, and its internally duplicated subdomains likely possess divergent characteristics. p43 represents a novel protein type (“dorylipophorin”) only known in Dorylaimia (Clade I) nematodes. We demonstrate that p43 is the dominant protein in Trichuris’s pseudocoelomic fluid, replacing the major internal lipid transporters of all other nematode clades, representing an ancient functional dichotomy. In Trichuris, and potentially other Clade I parasites of plants and animals, these proteins’ lipid-binding activities may be adapted for both internal physiological and external immunomodulatory activities.